2009
DOI: 10.1007/s10201-009-0277-5
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient ratios and phytoplankton community structure in the large, shallow, eutrophic, subtropical Lakes Okeechobee (Florida, USA) and Taihu (China)

Abstract: Analysis of ten-and four-year datasets for the large, shallow, subtropical, and eutrophic Lakes Okeechobee (USA) and Taihu (China), respectively, suggest that resource-ratio explanations for cyanobacteria dominance may not apply to these two lakes. Datasets were examined to identify relationships between nutrient ratios [total nitrogen (TN):total phosphorus (TP) and ammonium (NH 4 ? ):oxidized N (NO x )] and phytoplankton community structure (as proportions of cyanobacteria and diatoms to total phytoplankton b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
60
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(67 citation statements)
references
References 53 publications
6
60
0
1
Order By: Relevance
“…Upon death, the algae settle to the benthos and cause N loss through denitrification in the sediment bed, which, in return, amplifies N-limiting conditions . Although studies of other shallow lakes have found that N-fixing cyanobacteria may supplement N (Mccarthy et al, 2009), during periods of cyanobacterial blooms, past research showed that the proportion of N-fixing cyanobacteria and N fixation efficiency were low in Lake Taihu (Mccarthy et al, 2007;Paerl et al, 2011). Hence, N concentrations in Meiliang Bay may have had little supplementation in summer and fall (Fig.…”
Section: Interannual and Seasonal Changes Of Influent Nitrogen And Phmentioning
confidence: 97%
See 2 more Smart Citations
“…Upon death, the algae settle to the benthos and cause N loss through denitrification in the sediment bed, which, in return, amplifies N-limiting conditions . Although studies of other shallow lakes have found that N-fixing cyanobacteria may supplement N (Mccarthy et al, 2009), during periods of cyanobacterial blooms, past research showed that the proportion of N-fixing cyanobacteria and N fixation efficiency were low in Lake Taihu (Mccarthy et al, 2007;Paerl et al, 2011). Hence, N concentrations in Meiliang Bay may have had little supplementation in summer and fall (Fig.…”
Section: Interannual and Seasonal Changes Of Influent Nitrogen And Phmentioning
confidence: 97%
“…It is found that secondary N limitation was a transition phase that remained nearly a decade. In Lake Okeechobee, N reduction can drive blooms of N-fixing cyanobacteria (Mccarthy et al, 2009); therefore, to restore water quality in the lake, a plan was proposed to reduce P concentrations to create the historical natural P-limited conditions in Lake Okeechobee (Mccarthy et al, 2009). In Meiliang Bay, however, the cyanobacterial community is dominated by Microcystis spp., which is not an N-fixing species (Chen et al, 2003a;Chen et al, 2003b;Mccarthy et al, 2009).…”
Section: Seasonal Nutrient Limitation and Regulation Of Eutrophicationmentioning
confidence: 99%
See 1 more Smart Citation
“…N limitation occurred in summer and P limitation in winter, which affected the phytoplankton markedly (McCarthy et al, 2007;Xu et al, 2010). It was presumed that dominant species in Lake Taihu would shift from non-N 2 -fi xing Microcystis to potentially N 2 -fi xing cyanobacteria genera ( Anabaena and Aphanizomenon ) for N-limitation (or co-limitation) over the growing season (McCarthy et al, 2009). Most studies only focused on the bloom-forming species of Microcystis and the bloom-prone northern part.…”
Section: Introductionmentioning
confidence: 99%
“…Em reservatórios tropicais, diversos fatores como a RSFA disponível (HENRY et al, 2006;CUNHA & CALIJURI, 2011), o TDH (BEAVER et al 2013, temperatura (MCCARTHY et al, 2009), períodos de estratificação e de mistura da coluna de água (CALIJURI et al, 2002), parecem ser importantes para regular a comunidade fitoplanctônica. Especialmente em ambientes com maior estado trófico (HUSZAR et al, 2006 Não houve variação significativa entre as profundidades para a maioria das variáveis, apenas para RSFA e para a assimilação de ureia.…”
Section: A Comunidade Fitoplanctônicaunclassified